Pengaruh Promosi dan Kualitas Pelayanan Terhadap Minat Kunjung Pemustaka Pada Perpustakaan Daerah Merauke - Juventus Bangkit Wibowo; Nur Rohmah Yulia Ningrum (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2023)
The aim of this research is to analyze: 1) the influence of promotions on interest in visiting users at the Merauke Regency regional library; 2) the influence of service quality on user interest in visiting the Merauke Regency regional library; 3) the influence of promotion and service quality on user interest in visiting the Merauke Regency regional library. This research is quantitative research. The data collection technique used was a questionnaire. The population in this study was all library visitors in January-October 2022, totaling 3,520 people. The sampling technique uses Proportional Random Sampling. The sample size was determined using the Slovin formula and a sample of 97 respondents was obtained. Instrument testing in this research consisted of validity and reliability tests. The data analysis techniques used in this research are: 1) classic assumption tests consisting of normality tests, multicollinearity tests, and heteroscedasticity tests; 2) test the hypothesis using multiple linear regression. The results of the research show that: 1) there is a significant influence of promotion on the interest of visitors to the Merauke Regency regional library; 2) there is a significant influence of service quality on user interest in visiting the Merauke Regency regional library; 3) there is a significant influence of promotion and service quality on user interest in visiting the Merauke Regency regional library.